The Effect of Sustainability Report, Green Accounting, and Leverage on Corporate Values in Energy Sector Companies - Muhammad Farhan Maulana; Januar Eko Prasetio (AIBPM Publisher, 2025)
Energy businesses' economic operations undoubtedly have a direct influence on society, the environment, and the local community. Providing stakeholders with access to corporate information may benefit the business in a number of ways, including financially. This study aims to evaluate the impact of leverage, green accounting, and sustainability reports on corporate value. The corporate value, the study's dependent variable, uses the price-to-book value (PBV) ratio to calculate. In contrast, the independent variables that are employed, including the sustainability report, are quantified using CSRIj, green accounting using a PROPER, and leverage, which are measured using the debt-equity ratio (DER). The corporate website and Indonesia Stock Exchange (IDX) provided the data utilized in the study. Population studies consisted of energy businesses that were listed between 2020 and 2023 on the IDX. Using purposive sampling, this study sample was selected; therefore, 74 corporate data samples satisfied the criterion. The study's findings suggest that green accounting and sustainability reports have little impact on corporate worth. However, the value of the corporation is impacted by leverage. Therefore, investors pay more attention to financial aspects than non-financial aspects such as environmental and social disclosure. The combination of independent variables in this study shows that the effect on the dependent variable is still weak or limited, so further researchers need to use more varied combinations.